2007
DOI: 10.1111/j.1439-0531.2007.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐oestrus Hormone Profiles and Follicle Growth in Lactating Sows with Oestrus Induced by Intermittent Suckling

Abstract: This study describes follicle dynamics, endocrine profiles in multiparous sows with lactational oestrus compared with conventionally weaned sows (C). Lactational oestrus was induced by Intermittent Suckling (IS) with separation of sows and piglets for either 12 consecutive hours per day (IS12, n = 14) or twice per day for 6 h per occasion (IS6, n = 13) from day 14 of lactation onwards. Control sows (n = 23) were weaned at day 21 of lactation. Pre-ovulatory follicles (> or =6 mm) were observed in 100% of IS12, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 42 publications
4
36
0
Order By: Relevance
“…Current sows have a high ovulation rate of 20-25 on average (e.g. Town et al, 2005;Gerritsen et al, 2008), and, in sows that remain pregnant, also fertilization rates are normally considered to be very high (Soede et al, 1995). As a consequence, litter size of sows is pre-dominantly determined by the level of embryo mortality.…”
Section: Fertilitymentioning
confidence: 98%
“…Current sows have a high ovulation rate of 20-25 on average (e.g. Town et al, 2005;Gerritsen et al, 2008), and, in sows that remain pregnant, also fertilization rates are normally considered to be very high (Soede et al, 1995). As a consequence, litter size of sows is pre-dominantly determined by the level of embryo mortality.…”
Section: Fertilitymentioning
confidence: 98%
“…Multiparous sows tend to have larger follicles at weaning (~3.3 mm) than primiparous sows (2.5 mm; Langendijk et al, 2000b) and are less susceptible to compromised follicle development at weaning compared to primiparous sows (Gerritsen et al, 2008). Our results indicate that four out of 24 sows that were treated with P.G.…”
Section: Discussionmentioning
confidence: 64%
“…At 60 d of age the gastrointestinal tract increased considerably its relative weight respect to weaning (62.2 vs. 93.8 g/kg EBW, P b 0.001), probably as a result of the ingestion of solid feed as a single nutrient source for three and a half weeks. Gerritsen et al (2008) studied follicle dynamics and related endocrine profile in sows with lactational oestrus induced by two methods of IS during a prolonged lactation (41-45 days) in comparison with sows under continuous lactation and conventional weaning at day 21 of lactation. They concluded that sows subjected to IS were similar to weaned sows in timing of onset of oestrus, early follicle development and ovulation rate, but the pre-ovulatory LH surge and post-ovulatory progesterone increase was lower.…”
Section: Discussionmentioning
confidence: 99%